Balloon-Anchoring Technique to Stabilize Target Vessel Catheterization in Complex Endovascular Aortic Repair. (April 2020) - Heidemann, Franziska; Panuccio, Giuseppe; Tsilimparis, Nikolaos; Rohlffs, Fiona; Ahmed, Eltayeb Mohamed; Debus, E. Sebastian; Kölbel, Tilo
Purpose: To describe a bailout technique to stabilize target vessel catheterization in branched endovascular aortic repair.Technique: The technique is demonstrated in a 75-year-old patient with a 75-mm symptomatic type III thoracoabdominal aortic aneurysm that was treated with a t-Branch endograft. If a catheter cannot be advanced for exchange to a more stable guidewire after target vessel catheterization, the balloon-anchoring technique can be applied to stabilize the through-the-branch hydrophilic guidewire. Through a femoral access a catheter and hydrophilic wire are passed outside the device into the target vessel and exchanged with a stiff wire; a semicompliant balloon is advanced over the Rosen wire and inflated in the target vessel, stabilizing the through-the-branch hydrophilic wire and facilitating its exchange with a stiff wire over a catheter or advancement of the bridging covered stent directly.Conclusion: The balloon-anchoring technique adds to the spectrum of bailout techniques that can be applied in cases of challenging target vessel access.